Portrait of Indonesian language communication in the marginalized communities of the north coast of Central Java - Suciati, Sri; Umaya, Nazla Maharani (LITERA, 2025)
Indonesian, as the national language, plays an important role in communication throughout Indonesia, but its use in marginalized communities on the north coast of Central Java has rarely been studied. These communities consist of fishermen, small traders and low-income people who face social, cultural and economic challenges. This study aims to examine how they use Indonesian in their daily lives, the factors that influence them, such as local dialect, education level, and socio-economic conditions, as well as the impact of modernization on their language practices. The method used is descriptive qualitative with observation, interview, and documentation. A total of 193 respondents were involved, showing variations in language use based on education, gender, and social status. It was found that language practices reflect people's identity and survival strategies. The main focus of this research is the form and function of Indonesian language communication in reflecting the identity, adaptation, and resilience of marginalized communities in the midst of limitations.